ChemInform Abstract: Rhodium‐Catalyzed Cycloisomerization of 2‐Silylethynyl Phenols and Anilines via 1, 2‐Silicon Migration. Issue 32 (July 2016) - Kanno, Hiroshi; Nakamura, Kyosuke; Noguchi, Keiichi; Shibata, Yu; Tanaka, Ken
Abstract: affording silylbenzofurans and silylindoles